Proposing a process for training online teaching competence for lecturers at higher education institutions - Chi, Diep Phuong; Oanh, Duong Thi Kim (Journal of Education and e-Learning Research, 2023)
Online teaching has become an inevitable trend in education as technology and engineering advance. It is necessary to train and foster online teaching competence for lecturers at higher education institutions. This article uses the literature review and the theoretical method to analyze the existing proposals on models and frameworks of online teaching competency by many different authors worldwide. Based on the discovery of the commonalities and gaps between these perspectives combined with analyzing the characteristics of online teaching at the university level, the article proposes a framework of online teaching competencies for the higher education faculty along with relevant knowledge related to these competencies. This framework includes eight competencies with specific performance criteria. This article also builds a process for training online teaching competence for lecturers at higher education institutions. According to the PDCA deeming cycle, this process consists of three stages: planning, implementation and improvement to support lecturers in adapting to the virtual teaching environment.